Pathways to democracy after authoritarian breakdown: Comparative case selection and lessons from the past - Jean Lachapelle; Sebastian Hellmeier (International Political Science Review, 2022)
Mass movements that are able to overthrow a dictator do not always lead to democracy. Transition periods present narrow windows of opportunity in which activists face difficult decisions to build democracy and prevent authoritarian relapse. Existing scholarship offers limited guidance for pro-democracy forces because it focuses on unchangeable structural factors and cases with a known outcome. We propose an innovative approach for finding informative comparisons for ongoing transitions after authoritarian breakdowns. We quantify the similarity between all breakdowns caused by mass uprisings since 1945 based on their structural preconditions. We then apply our approach to Sudan's ongoing transition and draw lessons from two similar cases: the Philippines in 1986 (successful democratization); and Burma/Myanmar in 1988 (failed democratization). Our analysis shows that structural factors are weak predictors of transition outcomes and that Sudan shares characteristics with cases of both failed and successful democratization. Therefore, democratic transition appears possible in Sudan.
Keywords: 330; democratization; democratic transition; authoritarian breakdown; matching; mixed methods